Anastatoidae brachartonae gahan, a new pupal parasite of Nephantis serinopa Meyrick - Joy, P. J.; Joseph, K. J. (ENTOMON, 1976)
A pupal parasite Anastatoidae brachartonae (Hymenoptera, Chalcidoidae) has been recorded for the first time from Nephamis serinopa Meyrick the black-headed caterpillar pest of coconut in Kerala.